2020
DOI: 10.1038/s41398-020-01009-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polygenic risk for psychiatric disorders and smoking behaviour on psychotic experiences in UK Biobank

Abstract: While psychotic experiences are core symptoms of mental health disorders like schizophrenia, they are also reported by 5–10% of the population. Both smoking behaviour and genetic risk for psychiatric disorders have been associated with psychotic experiences, but the interplay between these factors remains poorly understood. We tested whether smoking status, maternal smoking around birth, and number of packs smoked/year were associated with lifetime occurrence of three psychotic experiences phenotypes: delusion… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Another study using the PRS-SZ and conducted in adults looked for interaction with other environmental factors, i.e. smoking status, without finding any GxE interaction (García-González et al, 2020). One hypothesis to explain the negative results of this GxE interaction study is that the PRS-SZ is not the appropriate tool for the study of GxE interaction in psychosis (Assary et al, 2018).…”
Section: Gene X Environment (Psychosocial Stressors) Interactionsmentioning
confidence: 90%
See 3 more Smart Citations
“…Another study using the PRS-SZ and conducted in adults looked for interaction with other environmental factors, i.e. smoking status, without finding any GxE interaction (García-González et al, 2020). One hypothesis to explain the negative results of this GxE interaction study is that the PRS-SZ is not the appropriate tool for the study of GxE interaction in psychosis (Assary et al, 2018).…”
Section: Gene X Environment (Psychosocial Stressors) Interactionsmentioning
confidence: 90%
“…Another study using the PRS-SZ and conducted in adults looked for interaction with other environmental factors, i.e. smoking status, without finding any GxE interaction (García-González et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study assessing the associations between momentary stress and subclinical psychotic symptoms showed that higher levels of PRS-SZ were associated with a higher intensity of symptoms after a momentary stress among controls (Schick et al, 2022). In the fourth study, the authors assessed the interaction between PRS-SZ and smoking status, but did not show significant association (García-González et al, 2020).…”
Section: Introductionmentioning
confidence: 99%